Cerebral Venous Thrombosis During Pregnancy: Tertiary Centre Experience - Jayyar, Lamyaa; Othman, Basil; Othman, Mohammad (British Journal of Healthcare and Medical Research, 2024)
Introduction: Cerebral venous thrombosis (CVT) is a rare variant of stroke in the general population, but an important subtype among pregnancy- and puerperium-related cases. Studies describing its risk factors and clinical characteristics are limited. The aim is to study the prevalence of CVT with pregnancy in King Salman Bin Abdulaziz Medical City (KSAMC) for the past 23 years. In addition, detailing the presentation, symptoms, diagnosis and management of these patients. Methods: This a retrospective study to review files of pregnant women who was diagnosed as having CVT between first of January 2000 and end of October 2023. Aiming to study the prevalence of CVT with pregnancy in the past 23 years. In addition, detailing the presentation, symptoms, diagnosis and management of these patients. Results: There is only one patient with CVT during pregnancy out of 410355 deliveries in the past 23 years. Patient was diagnosed using MRI- venography. She was started on LMWH and patient delivered vaginally baby boy in good condition. Discussion: prevalence of CVT during pregnancy is 0.0002% and the incidence is 1case / 10,000,000 pregnancy per year. Normal physiological changes during first trimester may increase the risk of CVT. Conclusion: This finding of this study may provoke researchers in the country to study CVT during pregnancy on the national level to study such and important neurological issue during pregnancy.